Determinants of Return on Assets in Indonesian Sharia Bank - Ependi Ependi (ProBisnis : Jurnal Manajemen, 2023)
This study uses a quantitative research method with a descriptive approach. The data used in this study are secondary, obtained from secondary sources such as research journals and financial reports of Bank Syariah Indonesia (BRI Syariah, Mandiri Syariah, and BNI Syariah) from 2016 to 2020. This research was conducted by PT Bank Syariah Indonesia Tbk. with a sample consisting of population data. The variables used in this study consist of Operational Costs to Operating Income (BOPO), Financing to Deposit Ratio (FDR), Third Party Funds (DPK), and Return On Assets (ROA). Multiple linear regression analysis was used to test the effect of each independent variable on the dependent variable. The results showed that BOPO had a negative and significant effect on ROA, while FDR and DPK had a negative but not significant impact on ROA. Simultaneously, these three variables have a significant influence on ROA. Based on these findings, it is suggested that Bank Syariah Indonesia pay attention to operational cost management by increasing efficiency and managing costs. Banks must also maintain a balance between financing and deposits to optimize FDR. Management of third-party funds needs to be optimized by considering optimal financing needs and diversifying sources of operating income. Banks must also consider external factors such as monetary policy and overall economic conditions.